Case Study: Applying Rapid Flow Cytometry Analysis to CAPD Effluent. Issue 5 (September 2018) - Mulroney, Kieran T.; Hall, Jarrad M.; McGuire, Amanda L.; Inglis, Tim J.J.; Chakera, Aron
Peritoneal dialysis (PD) peritonitis cases require rapid clinical interventions to ensure the best possible patient outcomes. Culture-dependent microbiology tools are slow and cannot provide clinicians with evidence to guide antimicrobial prescription practices in an appropriate time frame. Genotypic methods have met with limited success for analyzing continuous ambulatory PD effluent, with most centers still relying on culture-dependent microbiology. We present a case study in which we apply flow cytometry techniques to antibiotic-compromised effluent. We demonstrate, with supporting evidence, direct enumeration of bacterial and human immune cells, with results reported within 2 hours of receiving the clinical specimen.